Forrageamento diário e sazonal de Atta sexdens Linnaeus, 1758 (Hymenoptera: Formicidae) em eucaliptais nos biomas brasileiros - Abreu, Caroline Silva de (2015)
Eucalyptus plantations are important for the forest sector and its main pests are the leaf-cutting ants Atta and Acromyrmex. These ants have a wide geographic distribution in Brazil, but Atta sexdens has greater economic importance. The knowledge of the foraging patterns and the influence of climatic factors on these patterns is relevant to management of this ant. Then, the objective of this study was to evaluate the daily and seasonal pattern of foraging of Atta sexdens in eucalyptus plantations in the biomes Savannah, Atlantic Forest, Pampa and the transition between the Atlantic Forest and Savannah. Daily and seasonal foraging activities were evaluated in five colonies per biome during 48 hours each season, between 2013 and 2014.The number of workers returned to the nest was monitored for five minutes every hour. Samples of plant fragments transported by ants were collected for two minutes every two hours during a 24 hour cycle. The temperature and relative humidity were recorded at each observation. The foraging of A. sexdens was predominantly nocturnal, but it was daytime in winter in Pampa. The foraging maximum occurred between 19° to 25°C and between 70 and 95% RH. The plant biomass foraged was higher in areas influenced by the Atlantic Forest, although the largest fragment carried have been observed in Savannah areas. The foraging was different among biomes and seasons. The foraging activity was higher in summer and autumn. There was relationship between the number of ants with load and the fragment area with the nest size. Nests were not active at the same time, even under temperature and relative humidity favorable. These information are important to improve control strategies with formicid baits, allowing its application on period of greater activity of the nests to ensure a fast and efficient loading of baits and reduce their exposure to non-target organisms.